DAMPAK PENERAPAN REFRESHMENT TRAINING TERHADAP KINERJA KARYAWAN BAGIAN DESK COLLECTION PT. SWAKARYA INSAN MANDIRI - Gina Pramesti Regita Cahyani; Winna Sarikusumaningtyas (Bajang Institute, 2024)
Increasing employee performance is the basis for companies to remain able to compete. The performance that has been determined by central management is not achieved, which is a problem in this research. Refreshment training and employee performance are the factors studied in the performance of PT. Swakarya Insan Mandiri employees. The purpose of this research is to determine the effect of refreshment training on employee performance. The data collection method uses interviews with interview guidelines that have been previously provided to HRD and some employees of the PT. Swakarya Insan Mandiri Desk Collection Section. With a qualitative research approach, this research shows that refreshment training has an impact on the performance of PT. Swakarya Insan Mandiri. The suggestion is to periodically provide skills to employees to work over time, provide more than one potential position for promotion and provide benefits in accordance with current market trend conditions